2017
DOI: 10.7554/elife.18492
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activation of visual pigments in relation to openness/closedness of chromophore-binding pocket

Abstract: Visual pigments can be spontaneously activated by internal thermal energy, generating noise that interferes with real-light detection. Recently, we developed a physicochemical theory that successfully predicts the rate of spontaneous activity of representative rod and cone pigments from their peak-absorption wavelength (l max ), with pigments having longer l max being noisier. Interestingly, cone pigments may generally be~25 fold noisier than rod pigments of the same l max , possibly ascribed to an 'open' chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 16 publications
(35 reference statements)
3
50
0
Order By: Relevance
“…A recent study suggests that the ability to exchange of 11-cisretinal in a pigment with 9-cis-retinal in solution in the dark can be explained by the differences between the structures of the chromophore binding site (open or closed) (29). We assessed the degree of retinal exchange in rhodopsin, zebrafish blue, and Xenopus blue (Fig.…”
Section: Mechanistic Implication Of the Low Thermal Isomerization Ratesmentioning
confidence: 99%
“…A recent study suggests that the ability to exchange of 11-cisretinal in a pigment with 9-cis-retinal in solution in the dark can be explained by the differences between the structures of the chromophore binding site (open or closed) (29). We assessed the degree of retinal exchange in rhodopsin, zebrafish blue, and Xenopus blue (Fig.…”
Section: Mechanistic Implication Of the Low Thermal Isomerization Ratesmentioning
confidence: 99%
“…; Yue et al. ). The temperature dependence and physiological importance of these rod equilibria suggests that natural selection may alter rhodopsin stability as a means to modulate visual performance in response to natural temperature variation.…”
mentioning
confidence: 97%
“…to organismal visual sensitivity (20,35,36). We tested this experimentally using the prototypical class A GPCR model, bovine (Bos taurus) rhodopsin, because it is well characterized and allows interpretation of the functional results within well-resolved crystal structures (62)(63)(64).…”
Section: High-altitude Variants Are Near Important Structural Motifsmentioning
confidence: 99%
“…Recent evidence suggests that visual sensitivity within different habitats is likely maximized through natural variation shifting the spontaneous thermal-and light-activated decay rates of ligand-bound rhodopsin (28,33,34), two distinct kinetic processes of direct relevance to rod photosensitivity (17,20,21). Transgenic animal models have demonstrated that amino acid substitutions destabilizing these inactive and active-forms of rhodopsin can directly affect the dim-light sensitivity of rods (35,36), and are likely responsible for a reduction in rhodopsin-mediated dim-light visual performance in Significance Protein evolution in response to different environments has long been of interest to both evolutionary biologists and biochemists. High-altitude specialist catfishes in the Andes mountains offer an opportunity to examine the molecular adaptations accompanying adaptation to cold environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation